Differences in the Composition of the Rumen Microbiota of Finishing Beef Cattle Divergently Ranked for Residual Methane Emissions - Smith, Paul E.; Kelly, Alan K.; Kenny, David A.; Waters, Sinéad M. (Frontiers in Microbiology, 2022)
With the advent of high throughput technology, it is now feasible to study the complex relationship of the rumen microbiota with methanogenesis in large populations of ruminant livestock divergently ranked for enteric emissions. Of recent, residual methane emissions (RME), has been shown to be the optimal phenotype for assessing the methanogenic potential of ruminants, due to the trait’s independence from animal productivity. However, there is currently a dearth of data available on the bacterial and archaeal microbial communities residing in the rumen of animals divergent ranked for RME. Therefore, the objective of this study was to investigate the relationship of the rumen microbiota with RME in a population of finishing beef cattle. Methane emissions was estimated from individual animals, with the use of the GreenFeed Emissions Monitoring system, for 21 days over a mean feed intake measurement period of 91 days. Residual methane emissions was calculated for 282 crossbred finishing beef cattle, following which a ~30% difference in all expressions of methane emissions was observed between high and low RME ranked animals. Rumen fluid samples were successfully obtained from 268 animals during the final week of the methane measurement periods, using a trans-oesophageal sampling device. Rumen microbial DNA was extracted and subjected to 16S rRNA amplicon sequencing. Animals ranked as low RME had the highest relative abundance (P<0.05) of the lactic acid producing bacterial generas (Intestinibaculum, Sharpea, Olsnella) and Selenomas, and the lowest (P<0.05) proportions of Pseudobutyrivibrio, Butyrivibrio and Mogibacterium. Within the rumen methanogen community, an increased abundance (P<0.05) of the genera Methanosphaera as well as the Methanobrevibacter RO clade was observed in low RME animals. The relative abundances of both Intestinibaculum and Olsnella were negatively correlated (P<0.05) with RME and positively correlated with ruminal propionate. A similar relationship was observed for the abundance of Methanosphaera and the Methanobrevibacter RO clade. Findings from this study highlights the ruminal abundance of bacterial genera associated with the synthesis of propionate via the acrylate pathway, as well as the methanogens Methanosphaera and members of the Methanobrevibacter RO clade, as potential microbial biomarkers of the methanogenic potential of beef cattle.